Nocturnal sweating—a common symptom of obstructive sleep apnoea: the Icelandic sleep apnoea cohort - Thorarinn Gislason; Christer Janson; Erla Bjornsdottir; Bryndis Benediktsdottir; Erna Sif Arnardottir; Sigurdur Juliusson; Samuel T Kuna; Allan I Pack (BMJ Open)
Objectives To estimate the prevalence and characteristics of frequent nocturnal sweating in obstructive sleep apnoea (OSA) patients compared with the general population and evaluate the possible changes with positive airway pressure (PAP) treatment. Nocturnal sweating can be very bothersome to the patient and bed partner.Design Case–control and longitudinal cohort study.Setting Landspitali—The National University Hospital, Iceland.Participants The Icelandic Sleep Apnea Cohort consisted of 822 untreated patients with OSA, referred for treatment with PAP. Of these, 700 patients were also assessed at a 2-year follow-up. The control group consisted of 703 randomly selected subjects from the general population.Intervention PAP therapy in the OSA cohort.Main outcome measures Subjective reporting of nocturnal sweating on a frequency scale of 1–5: (1) never or very seldom, (2) less than once a week, (3) once to twice a week, (4) 3–5 times a week and (5) every night or almost every night. Full PAP treatment was defined objectively as the use for ≥4 h/day and ≥5 days/week.Results Frequent nocturnal sweating (≥3× a week) was reported by 30.6% of male and 33.3% of female OSA patients compared with 9.3% of men and 12.4% of women in the general population (p<0.001). This difference remained significant after adjustment for demographic factors. Nocturnal sweating was related to younger age, cardiovascular disease, hypertension, sleepiness and insomnia symptoms. The prevalence of frequent nocturnal sweating decreased with full PAP treatment (from 33.2% to 11.5%, p<0.003 compared with the change in non-users).Conclusions The prevalence of frequent nocturnal sweating was threefold higher in untreated OSA patients than in the general population and decreased to general population levels with successful PAP therapy. Practitioners should consider the possibility of OSA in their patients who complain of nocturnal sweating.